A Study of Ta-Si-N/Ti Bilayer Diffusion Barrier for Copper/Silicon Contact Systems. Issue 8 (10th June 2016) - Ding, Minghui; Zheng, Hang; Wang, Li; Zhang, Hongsen
Abstract : Ta-Si-N (10 nm)/Ti (20 nm) bilayer film has been designed with the purpose of using as diffusion barrier in copper interconnection. Ta-Si-N/Ti bilayer diffusion barriers were deposited on the substrate of n-type (100) silicon wafer using radio-frequency (RF) magnetron sputtering, followed by in situ deposition of copper. To investigate the thermal stability of the Ta-Si-N/Ti diffusion barriers, annealing was subsequently conducted in N2 gas for 60 min and annealing temperatures were chosen at 600°C, 650°C, 700°C, 750°C, and 800°C. X-ray diffraction (XRD) revealed that Ta-Si-N layer grown on the Ti layer exhibited an amorphous phase. The results indicated that Ta-Si-N/Ti film can prevent copper diffusion at 750°C. After annealing at 750°C, the production of Ti-Si layer can effectively decrease contact resistance between barrier and silicon.